La 72: an oasis along the migration routes in Mexico - Olayo-Méndez, A (Refugee Studies Centre, University of Oxford, 2017)
Locally run shelters along the migration routes in Mexico provide sorely needed respite and support. In the face of violence, stricter migration policies and daily obstacles, those working at the La 72 shelter strive to respect people’s sense of dignity while caring for their safety.